Attitude and Behaviour Towards Littering; A Case Study of Klottey Korle Residents - Obiri, Emma Aku (UniMAC-GIJ, 2020)
The littering problem is an inherent fact of modern living that exists in one way or another in many countries, cities, and communities of the world. In Ghana, urban littering especially is one of the most visible and persistent environmental issues facing the government and costs the government several millions of cedis each year to clean up and repair the damages associated with it. Studies done have continually shown that littering is a result of attitudinal and behavioral problems in human beings and as such, it is seen as a human impact on the environment and the society; a personal choice with public consequences. Over the years, the government of Ghana has implemented a range of strategies to tackle the litter problem. Some of these are the introduction of a National Sanitation day, distributing dustbins to households, prohibiting littering, monitoring, arresting, and fining of individuals who litter, among others. However, these solutions have not been as effective as they lack community participation. Furthermore, they do not focus nor seek to understand citizen’s attitudes and behavior towards littering. The purpose of this project which focused on Klottey Korle was guided by four main objectives; (1) to ascertain the nature and extent of littering in Klottey Korle, (2) to determine Klottey Korle residents’ attitude and behavior towards littering, (3) to assess the effect of littering in Klottey Korle, (4) to recommend solutions to curb the littering problem The study findings were largely based on asurvey of households sampled from Osu, Adabraka, and Asylum down in Klottey Korle. The research findings revealed that people and keeping trash by the roadside are the major sources of litter in Klottey Korle. The study also revealed that the residents had both positive and negative behavior towards littering. The study recommends more community engagement and dialogue, awareness creation through civic education which should target all citizens, and the provision of more litter bins.
Thesis